Human resources accounting optimization: A conceptual pathway to improve financial performance - Sari, Juwita; Yani, Prawita; Pradhani, Fastha Aulia (Journal of Business & Banking, 2023)
This research discussed HRA’s impact on a company’s financial performance. Human Resource Accounting (HRA) is measured by using 16 indicators, while financial performance uses 4 indicators, which consist of return on assets (ROA), return on equity (ROE), firm size, and leverage ratio. The analytical method used is binary logistic regression. The result shows that none of the HRA indicators affect ROA, while the other three are still affected by HRA indicators. Employment report indicators and other employee benefits in HRA indexes significantly affect ROE. Human resource policy, human resource development fund, and superannuation fund affect firm size the most. The last leverage ratio is significantly affected by human resource policy. This research has implications for manufacturing companies to increase information transparency for investors in the capital market through the sustainability disclosure of periodical HRA reports. Meanwhile, it is recommended that the government take action to encourage HRA disclosure for public companies in Indonesia by making the standards and regulations needed.